2020
DOI: 10.1097/j.pain.0000000000001966
|View full text |Cite
|
Sign up to set email alerts
|

Individuals with chronic pain have the same response to placebo analgesia as healthy controls in terms of magnitude and reproducibility

Abstract: This is a repository copy of Individuals with chronic pain have the same response to placebo analgesia as healthy controls in terms of magnitude and reproducibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 55 publications
0
9
0
1
Order By: Relevance
“…It is known that patients affected with chronic or neuropathic pain do not respond to pharmacological treatments [119]. However, recent research has suggested that individuals with chronic pain exhibit a similar placebo analgesic response (magnitude and reliability) to that exhibited by healthy controls [120]. Suppose our results are also valid for patients suffering from chronic pain with relatively low levels of active avoidance or fear personality traits.…”
Section: Discussionmentioning
confidence: 52%
“…It is known that patients affected with chronic or neuropathic pain do not respond to pharmacological treatments [119]. However, recent research has suggested that individuals with chronic pain exhibit a similar placebo analgesic response (magnitude and reliability) to that exhibited by healthy controls [120]. Suppose our results are also valid for patients suffering from chronic pain with relatively low levels of active avoidance or fear personality traits.…”
Section: Discussionmentioning
confidence: 52%
“…Secondly, the fact that dynamic changes in pain perception in both groups are best explained by different models also presents an interesting research avenue. Placebo analgesia gives insight into the endogenous pain modulation mechanisms [3], and it has been observed that great variability exists in the placebo response of patients [18]. This could indicate that different factors could be leading to dynamic changes in the pain perception of different patients, and therefore, it may be taken as an argument in favour of individualised or stratified medicine, widely considered an important goal in clinical pain science [21].…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon can provide insight into endogenous pain modulation mechanisms [3], which are important markers of chronic pain vulnerability, disability and treatment outcome [25]. Since considerable variability exists in the placebo response between individuals [16,18,24], understanding the differences in pain perception between those who are sensitive to placebo analgesia (responders) and those who are not (nonresponders) could help in the understanding of individual differences in endogenous pain control and treatment outcome.…”
Section: Introductionmentioning
confidence: 99%
“…While the effects of different sham stimulations on neural networks need to be further investigated, a placebo effect might be involved if those sham stimulations are experienced differently on the scalp. Studies examining whether chronic pain populations, including FMS, are more responsive to placebo than non-pain healthy controls show mixed findings [59][60][61] ; however, a systematic review investigating placebo-intervention against notreatment comparator groups in FMS found that the magnitude of placebo effects increases with the effect size of the active treatment 62 . While it is possible that a higher intensity sham stimulation would give rise to a stronger placebo response, we observed no significant differences in participants' guesses as to whether they received sham or active treatment between either sham group nor the active group.…”
Section: Discussionmentioning
confidence: 99%